1992
DOI: 10.1021/jm00100a034
|View full text |Cite
|
Sign up to set email alerts
|

4-[2-[Methyl(2-phenethyl)amino]-2-oxoethyl]-8-(phenylmethoxy)-2-naphthalenecarboxylic acid: a high affinity, competitive, orally active leukotriene B4 receptor antagonist

Abstract: Leukotriene B4 is a potent activator for polymorphonuclear (PMN) 1eukocytes.l It causes increased chemotactic and chemokinetic migration, aggregation, degranulation, lysosomal enzymes release, and free radical release. Because of these biological activities, LTB4 may play an important role in inflammatory diseases in which elevated levels of LTB4 have been detected, such as inflammatory bowel disease, rheumatoid arthritis, and psoriasis. The effects Of LTB4 are mediated through high-and low-affinity receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…By Scatchard analysis, 2a exhibited K i s of 0.14 and 2 nM for guinea pig and human PMN LTB 4 receptors, respectively. 2 SAR study of 2a was carried out in a manner similar to that described for 4a, and in general the results paralleled those obtained for the indole series. Thus, compounds 2b and 2c again demonstrated the importance of the substitution pattern on the central ring.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…By Scatchard analysis, 2a exhibited K i s of 0.14 and 2 nM for guinea pig and human PMN LTB 4 receptors, respectively. 2 SAR study of 2a was carried out in a manner similar to that described for 4a, and in general the results paralleled those obtained for the indole series. Thus, compounds 2b and 2c again demonstrated the importance of the substitution pattern on the central ring.…”
Section: Resultssupporting
confidence: 57%
“…1 We have reported the synthesis RG 14893 (2a), a potent competitive LTB 4 receptor antagonist with oral inhibitory activity of the chemotaxis of PNMs to the LTB 4 -induced wheals in guinea pigs. 2 In the preceding paper 3 we have also described the development and structure-activity relationship study of a class of LTB 4 antagonists based on the phenylacetamide 3. Our study established that three structural features, namely (a) the 2-[methyl(2phenethyl)amino]-2-oxoethyl side chain, (b) an acid function, and (c) an additional lipophilic group, are required for high binding affinity with LTB 4 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that 1 inhibited the GP spleen membrane and intact human PMN binding resulting in IC 50 values of 0.4 nM (vs 0.5 nM ligand) and 4.7 nM (vs 0.5 nM ligand), respectively. 3 In addition, 1 also exhibited an IC 50 of 0.96 nM in a GP whole cell PMN binding assay and, in a functional assay, it inhibited 1 nM LTB 4 -induced GP PMN aggregation with an IC 50 of 0.8 nM. The strong correlation between the binding affinity and functional antagonistic activity demonstrated that this compound is both a receptor binder and functional antagonist.…”
Section: Resultsmentioning
confidence: 84%
“…2 Recently, we reported that RG 14893 is a potent LTB 4 receptor antagonist with oral activity. 3 The synthesis of this compound evolved from our initial observation that a simple phenylacetamide derivative 2 displayed moderate competitive antagonist activity with an IC 50 of 4.7 µM in a broken-cell human polymorphonuclear leukocyte (PMN) LTB 4 binding assay. This unexpected activity led us to speculate that 2 had unusual structural features which could contribute to the binding affinity to the LTB 4 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…13 The chiral LTB4 receptor antagonist SC-53228 (6, K = 1.3 nM) has been reported by Searle,14 and Rhdne-Poulenc Rorer has reported that RG 14893 (7) has a K of 2 nM on human PMNs. 15 The LTB4 receptor antagonist effort was initiated with the objective to discover novel antiinflammatory agents. As previously reported, using LTB4 (1) as a structural template the program quickly produced compounds with high receptor affinity.…”
mentioning
confidence: 99%